Starless & Silver: The Abstraction of Fetish as It Occurs Through Analogue Photographic Means - Nagra, Jes-ci (Auckland University of Technology, 2011)
This visual arts research project utilises analogue photographic methods, specifically black and white photographic processes of still and moving image to examine the relationship between photography, fetish and the stage. Differentials in the term ‘fetish’ are investigated to locate the operation of fetish; these include fetishism and fetishisation. These terms are explored to identify how analogue photographic means could align itself with the operation of fetish, through ritual, object and ‘protection against loss’. Using the subject matter of the stage that has been fabricated as part of this project, Starless and Silver explores the anticipation and expectation of both the stage and the photographic image, and inturn observes the formation of an unrequited viewing experience.
Keywords: Analogue Photography; Fetish; Black; White; Photography; Cine; Moving Image; Medium Format; Silver; Object; Illusion; Stage